Advanced Nanoscale Functionalities for Water and Energy Technologies - Xu, Zhi; Wu, Nan; Abdelghani‐Idrissi, Soufiane; Trégouët, Corentin; Perez‐Carvajal, Javier; Colin, Annie; Ma, Ming; Niguès, Antoine; Siria, Alessandro (Advanced Physics Research, 2025)
Nanofluidics, the study of fluid behaviors under nanoscale confinement, is driving transformative innovations in water and energy technologies. This rapidly evolving field leverages unique physical and chemical phenomena such as enhanced ion transport and tunable fluid interactions, enabling breakthrough advancements in critical applications. This review provides a comprehensive overview of theoretical frameworks and technological innovations facilitated by nanofluidics, highlighting its implications across diverse domains. Key applications include water treatment and desalination, where advanced nanostructured materials enable superior selectivity and efficiency in molecular and ionic separations. The principles of nanofluidics also offer new pathways for renewable energy generation, including harvesting osmotic energy and optimizing energy storage systems. Additionally, the integration of nanofluidics into carbon dioxide capture and utilization processes has opened new horizons for addressing climate change by enhancing reaction efficiencies and facilitating sustainable resource cycles. By bridging fundamental nanoscale science with innovative applications, nanofluidics presents a transformative approach for addressing global challenges in water security, sustainable energy, and environmental management. The review concludes by discussing scaling challenges, interdisciplinary opportunities, and the promising future directions of nanofluidic technologies for sustainable development. Nanofluidics explores fluid and ion transport under nanoscale confinement, driving advancements in water treatment and energy technologies. With applications in high‐efficiency desalination, osmotic energy generation, and scalable energy storage, it leverages unique material properties and confinement effects to address critical challenges in sustainability and resource management.